Tackling for Human Trafficking: Village-based Movement of Migrant Workers in Lembata, Indonesia - Lindra Darnela; Ahmad Tholabi Kharlie (Jurnal Cita Hukum, 2023)
Studies on the role of villages in tackling human trafficking are not widely discussed. This study investigated the efforts of grassroots in tackling human trafficking in Lembata, Indonesia. The data based on observations, interviews with the governments, and discussions with six migrant worker communities in Lembata. This study proved that village community in Lembata had succeeded in providing an alternative livelihood for former migrant workers through strengthening the productive economy. The community was also able to provide guidance and escort to prospective migrant workers to recognize their rights and obligations as migrant workers. The village community had also succeeded in advocating the government to fulfill its obligations in protecting prospective migrant workers and/or migrant workers. Thus, the bottom-up system is an effective way of tackling trafficking.